2021
DOI: 10.1088/1748-9326/ac0748
|View full text |Cite
|
Sign up to set email alerts
|

Climate sensitivity indices and their relation with projected temperature change in CMIP6 models

Abstract: Equilibrium climate sensitivity (ECS) and transient climate response (TCR) are both measures of the sensitivity of the climate system to external forcing, in terms of temperature response to CO2 doubling. Here it is shown that, of the two, TCR in current-generation coupled climate models is better correlated with the model projected temperature change from the pre-industrial state, not only on decadal time scales but throughout much of the 21st century. For strong mitigation scenarios the difference persists u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…By 2100, the difference in 2-m air temperature anomalies between two model versions reaches around 1.5 K. The greater value around 6.0 K is achieved by a model with higher sensitivity. This is consistent with Huusko et al (2021); Grose et al (2018); Forster et al (2013), which confirmed that future projections show a stronger relationship than historical ones between warming and climate sensitivity. In contrast to feedback strength, which is more important in forecasting future temperature change, historical warming is more associated with model forcing.…”
Section: Near Surface Air Temperature Changesupporting
confidence: 89%
“…By 2100, the difference in 2-m air temperature anomalies between two model versions reaches around 1.5 K. The greater value around 6.0 K is achieved by a model with higher sensitivity. This is consistent with Huusko et al (2021); Grose et al (2018); Forster et al (2013), which confirmed that future projections show a stronger relationship than historical ones between warming and climate sensitivity. In contrast to feedback strength, which is more important in forecasting future temperature change, historical warming is more associated with model forcing.…”
Section: Near Surface Air Temperature Changesupporting
confidence: 89%
“…The higher climate sensitivity of NZESM means that global mean surface temperature will increase more strongly with greenhouse gas emissions than considered realistic. Recent results suggest that in particular surface temperature changes in tropical regions are more directly impacted by the higher climate sensitivity than in the Southern Ocean (Huusko et al, 2021). Instead of a multimodel approach (Alexander et al, 2018;Holbrook et al, 2019; Oliver et al, 2019;Hayashida et al, 2020;Plecha and Soares, 2020), an ensemble approach has been used in this regional study, with three ensemble members in each SSP, to explore the solution space of MHW projections in an eddy permitting system.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Moreover, Huusko et al . 66 showed that under the SSP2-4.5 scenario, the TCR is a better predictor of regional warming throughout the 21st century. From the 60 models with both historical air temperature trends and TCR estimates, we excluded the 21 with both estimates outside the likely range.…”
Section: Methodsmentioning
confidence: 99%